Outdoor Amphitheater Planning in Mastplan Activities using Autocad 2 D and Sketchup 3 D Applications - Misdar Alamsyah; Muhammad Syarif; Mohd Hazwan (Jurnal Teknik Sipil dan Perencanaan, 2024)
SMK Negeri 1 Sebatik Barat is a school expected to realize SMK Agrotourism, which has a land area of about 35 Hectares. The research "Outdoor Amphitheater Planning In Mastplan Activities Using Autocad 2D And Sketchup 3D Applications” itself was developed so that the existing land can be utilized properly, which planning uses 2D (Autocad) and 3D (SketchUp) applications. The object of this research is Liang Bunyu, West Sebatik, Nunukan Regency, North Kalimantan. Data collection uses primary methods where data is collected directly. The results of this study indicate that SMK Negeri 1 Sebatik Barat requires an Outdoor Amphitheater design plan to support the acceleration of the realization of SMK Agrotourism quickly.